Sharia Financial Performance Perspective: Business or Compliance Oriented - Neny Tri Indrianasari; Novi Puspitasari; Hari Sukarno (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2022)
There is a lot of controversy inthe literature on how to measure the performance of an Islamic Bank (IB). In short, the business model of Islamic banks is different from that of traditional banks. Therefore, the effectiveness of Islamic banks should be measured using the Sharia approach. One of the important pillars of the development of Sharia banking is Sharia compliance. Pillar this is the main difference between Islamic banks and traditional banks. A sharia supervisory board, or sharia supervision, is necessary to ensure the implementation of sharia principles in banking institutions. In this article, we consider the zakat (Islamic tax) as an alternative indicator for measuring the effectiveness of Islamic banks. Zakat in business is very important, both from an Islamic point of view and from the point of view of poverty reduction. Zakat spending by banks can enhance the image of Islamic banks that exist as banking companies operating in accordance with Islamic law.